Saudi university environmental sustainability policies: Critical discourse analysis of responsibility frames and institutional voice - Alowayyid, Norah Nasser Saleh; Ibrahim, Khaled Ahmed Abdel-Al; Ali Doum, Hamed Mohammed; Koka, Nisar Ahmad; Alharahsheh, Abdulraoof Meqbel; Ismail, Sayed M (Research Journal in Advanced Humanities, 2026)
Saudi universities increasingly present environmental sustainability as part of institutional strategy, national development, campus management, research, and public responsibility. Yet policy language does more than describe environmental action: it assigns agency, calibrates obligation, and constructs a public voice through which the university appears as guardian, educator, manager, partner, or leader. This article examines those functions through a critical discourse analysis of an expanded Arabic corpus comprising 33 policy-facing texts or independently headed sections from seven Saudi universities. After navigation material and duplicated wording were removed, the corpus contained 1,960 running Arabic words and 119 analyzable clauses or list items. The data were coded for responsibility frame, social actor, modality, institutional voice, and legitimation strategy. All Arabic examples are presented in reader-oriented Romanization followed by English translation. The analysis identifies measurement and accountability, national and global alignment, institutional stewardship, education and research, and resource management as the most frequent primary frames. However, the dominant voice is not uniformly binding. Aspirational constructions such as “the university seeks,” “is keen,” and “aims” occur more often than explicit obligations, deadlines, or sanctions. Stronger passages name committees, units, programme owners, indicators, and reporting procedures; weaker passages foreground effort, leadership, rankings, or awareness while leaving operational responsibility diffuse. The article argues that Saudi university sustainability discourse often produces responsibility without fully specifying accountability. It concludes with a practical model for clearer policy writing that names responsible actors, distinguishes commitment from aspiration, balances individual conduct with institutional duty, and reports progress, limits, and trade-offs in language that campus communities can use.